Accuracy of sonographic criteria for diagnosis of adenomyosis in perimenopausal women with menorrhagia - Ahmed Mohammed Abdel Hak (Middle East Fertility Society Journal, 2010)
Objective: To determine the accuracy of transvaginal ultrasound in the diagnosis of uterine adenomyosis in women with menorrhagia. Design: Prospective observational clinical trial. Setting: Kasr El-Aini Hospital, Cairo University. Participants and interventions: Fifty perimenopausal women with menorrhagia were divided into two groups: those who have received hormonal therapy for menorrhagia (21 cases) and those who received nothing. Transvaginal sonography was done for all cases and correlation with histopathological assessment done after hysterectomy. Results: Transvaginal US had a sensitivity of 83%, a specificity of 86%, and a positive and negative predictive value of 66% and 94%, respectively. The diagnosis of adenomyosis uteri of the 10 patients with true-positive findings at US, the myometrium demonstrated heterogeneous and hypoechoic areas with or without the presence of cysts in 10 (100%) patients, hypoechoic areas with cysts in 5 (50%) patients, linear striation and globular uterus in 5 (50%). Eleven out of 12 (91%) cases of adenomyosis had an enlarged uterus. Conclusion: Adenomyosis of the uterus can be accurately diagnosed with transvaginal US with use of specific sonographic criteria. It is safe, available and cheap modality of diagnosis.